2007
DOI: 10.1016/j.soilbio.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of harvesting and logging slash on nitrogen and carbon dynamics in soils from upland spruce forests in northeastern Ontario

Abstract: The potential impact of timber harvesting in the boreal forest on aquatic ecosystem water quality and productivity depends in part on the production of nutrients within the soil of the harvested catchment. Nitrogen supplied by organic matter decomposition is of particular interest because of the important role that N plays in biotic processes in surface waters, and in forest nutrition in general. Logging slash quality and input to the forest floor has the potential to influence N availability after harvest on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…In terms of NH 4 + and NO 3 -, the absence of a relationship is not surprising in that the annual riparian zone mineral soil water N concentrations for the extensive sites were extremely low in this boreal ecosystem when contrasted with other forest types (Van Miegroet et al 1992;Foster et al 2005). Low net mineralization potential, especially for NO 3 -, for the F horizon and 0-10 cm of mineral soil from unharvested stands at the ELRA has been reported by Hazlett et al (2007). Of significant note were forest floor percolate NH 4 + and NO 3 -concentrations and mineral soil water NO 3 -concentrations at sites with alder present that were as high or higher than concentrations determined in a N-rich tolerant sugar maple (Acer saccharum Marsh.)…”
Section: Controls Of Soil Water N and C Concentrationsmentioning
confidence: 73%
See 2 more Smart Citations
“…In terms of NH 4 + and NO 3 -, the absence of a relationship is not surprising in that the annual riparian zone mineral soil water N concentrations for the extensive sites were extremely low in this boreal ecosystem when contrasted with other forest types (Van Miegroet et al 1992;Foster et al 2005). Low net mineralization potential, especially for NO 3 -, for the F horizon and 0-10 cm of mineral soil from unharvested stands at the ELRA has been reported by Hazlett et al (2007). Of significant note were forest floor percolate NH 4 + and NO 3 -concentrations and mineral soil water NO 3 -concentrations at sites with alder present that were as high or higher than concentrations determined in a N-rich tolerant sugar maple (Acer saccharum Marsh.)…”
Section: Controls Of Soil Water N and C Concentrationsmentioning
confidence: 73%
“…Previous work has demonstrated that organic and mineral soils at the site have the potential to release N after harvest (Hazlett et al 2007); however, it is uncertain to what extent this N will be microbially immobilized or taken up by regenerating vegetation within clearcut areas and, therefore, what amount will move into the riparian buffers downslope. The ability of riparian forests and soils on shallow and steep slopes to modify soil water concentrations under increased inputs from cutover areas could be dissimilar to that which was observed for the unharvested forest.…”
Section: Riparian Buffersmentioning
confidence: 99%
See 1 more Smart Citation
“…The warm, mesic, and aerated conditions created from timber harvesting operations are ideal for microbial metabolism and their mineralization of organic matter. The rate and timing of decomposition is also constrained by the amount of organic material left following harvest and its quality (i.e., more easily degradable leaf or needle litter and fine roots vs. less easily degradable branches and stems) (Hazlett et al 2007). The amount and type of residue (slash) retained on the site will differ depending on timber harvest approach and whether whole tree (de-limbing at road, less residue in plot) or tree-length (delimbed where cut, more residue on plot) methods were used.…”
Section: Dissolved Organic Carbon and Nutrientsmentioning
confidence: 99%
“…Treatments that suppress vegetation for extended periods or cause extensive exposure of mineral soil and/or compaction or rutting will have longer-term (≥10 yrs) effects (Bormann and Likens 1979). However, since the relationship between a specific vegetation management treatment and the mineralization of a given element depends on many variables, it is difficult to determine how any given element will respond (Hazlett et al 2007).…”
Section: Soil and Soil Nutrientsmentioning
confidence: 99%